Changes in chemical and structural composition of sugarcane bagasse caused by alkaline pretreatments [Ca(OH)2 and NaOH] modify the amount of endoglucanase and β-glucosidase produced by Aspergillus niger in solid-state fermentation. Issue 5 (4th May 2022) - Alarcón, Enrique; Hernández, Christian; García, Gabriela; Ziarelli, Fabio; Gutiérrez-Rivera, Beatriz; Musule, Ricardo; Vázquez-Marrufo, Gerardo; Gardner, Terrence G.
Abstract: The aim of this study was to evaluate the treatment effects of Ca(OH)2 solutions applied at different concentrations (2.5%, 5%, and 7.5%) on the structural and chemical composition of sugarcane bagasse (SCB). The feasibility of using the SCB as a substrate for endoglucanase and β-glucosidase production by Aspergillus niger through solid-state fermentation was also assessed. Sodium hydroxide (NaOH) 5% was used as a positive control/benchmark. Changes in SCB cell wall compositions was determined using 13 C solid-state nuclear magnetic resonance. While cellulosic fiber content and the production of endoglucanase (345.01 ± 139 U.gDM −1 ) increased using Ca(OH)2 as pretreatment for sugarcane bagasse, hemicellulose, lignin, alkyl C and carboxyl C content decreased. Comparisons between pretreated and non-pretreated SCB revealed that the highest values of β-glucosidase (58.18 ± 9.86 U.gDM −1 ) occurred in non-pretreated samples. The SCB pretreated with NaOH resulted in the highest delignification values (-49.88%) and the greatest hemicellulose remotion (-53.47%). However, this treatment also increased crystallinity index (CI; + 23.61%) in cellulose and showed the lowest endoglucanase (22.79 ± 11 U.gDM −1 ) and β-glucosidase (4.71 ± 1.44 U.gDM −1 ) activities. This study claims that cellulose CI, hemicellulose, and other nutrients (e.g., amino acids) are important variables that should be considered along with delignification, in the substrates selection for cellulase production using filamentous fungi.